OPTIMAL CONTROL ON CHOLERA DISEASE SPREADING MODEL WITH THREE VARIABLES CONTROL VARIATION - Fitria, Irma; Atlanta, Talitha B; Azahra, Nadia; Agustina, Choiriyah; Subchan, Subchan; Cahyaningtias, S (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Cholera is an infection of the small intestine by some strains of the bacterium Vibrio Cholerae. This disease is a deadly disease that necessitates efficient prevention and control measures. In this research, the optimal control of the cholera spread model with variations of three control variables is discussed. There are four controls to minimize the spread of diseases such as sanitation, treatment consisting of quarantine, increased education, and chlorination. The dynamic system is formed with three controls variation. Then it is compared and analyzed for the most effective result. The optimal control solution is derived using the Pontryagin Minimum Principle and solved using the Runge-Kutta method.